Strategies for active and passive pediatric RSV immunization - Katherine M. Eichinger; Jessica L. Kosanovich; Madeline Lipp; Kerry M. Empey; Nikolai Petrovsky (SAGE Publishing, 2021)
Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infections in children worldwide, with the most severe disease occurring in very young infants. Despite half a century of research there still are no licensed RSV vaccines. Difficulties in RSV vaccine development stem from a number of factors, including: (a) a very short time frame between birth and first RSV exposure; (b) interfering effects of maternal antibodies; and (c) differentially regulated immune responses in infants causing a marked T helper 2 (Th2) immune bias. This review seeks to provide an age-specific understanding of RSV immunity critical to the development of a successful pediatric RSV vaccine. Historical and future approaches to the prevention of infant RSV are reviewed, including passive protection using monoclonal antibodies or maternal immunization strategies versus active infant immunization using pre-fusion forms of RSV F protein antigens formulated with novel adjuvants such as Advax that avoid excess Th2 immune polarization.